Three-Stage Masquelet Technique and One-Stage Reconstruction to Treat Foot and Ankle Tuberculosis. (March 2020) - Qu, Wenqiang; Wei, Chi; Yu, Li; Deng, Yu; Fu, Panfeng; Kang, Zhe; Zhu, Shaobo
Background: The purpose of this article was to report the feasibility and effectiveness of 3-stage Masquelet technique and 1-stage operation for different stages of foot and ankle tuberculosis (TB). Methods: Ten consecutive patients with foot and ankle TB were retrospectively analyzed between January 2014 and December 2018. Five patients were treated with the 3-stage Masquelet technique, including thorough debridement with vacuum sealing drainage, implantation of antibiotic cement spacer, and subsequent reconstruction. Five patients were treated with a 1-stage reconstruction. The American Orthopaedic Foot & Ankle Society (AOFAS) and visual analog scale (VAS) pain scores were recorded at the last follow-up. The follow-up was 30.3 ± 17.8 months. Results: No reactivation of TB was observed in any patients. For the 3-stage operation group, 1 patient developed a distal tibia fracture. The duration of anti-TB therapy was 12.0 ± 0.8 months. The AOFAS score increased from 39.5 ± 9.9 preoperatively to 75.3 ± 7.0 postoperatively ( P < .05). The VAS pain score decreased from 6.3 ± 1.9 to 1.5 ± 1.3 ( P < .05). For the 1-stage operation, 1 patient had wound necrosis. The duration of anti-TB therapy was 13.8 ± 1.1 months. The AOFAS score increased from 51.8 ± 15.0 to 81.8 ± 6.3 ( P < .05). The VAS pain score decreased from 5.4 ± 1.1 to 1.0 ± 0.7 ( P < .05). Conclusion: Three-stage operation was effective for foot and ankle TB with stage IV, sinus tracts or other infections, and 1-stage reconstruction was effective for early-stage TBs. Level of Evidence: Level IV, case series.